Psychological Capital: Buffering the Longitudinal Curvilinear Effects of Job Insecurity on Performance - Lopez-Bohle, S (Elsevier B.V., 2017)
Job insecurity is a psychosocial risk that can present significant problems for organizational performance and employees’ health and well-being. The purpose of the current research was to investigate the curvilinear relationship between employee job insecurity and three types of job performance: in-role task performance, organizational citizenship behaviors directed to the organization (OCB-O), and organizational citizenship behaviors directed toward individuals (OCB-I). Additionally, we tested whether a higher order construct, Psychological Capital, consisting of hope, self-efficacy, resilience, and optimism would moderate the relationships between job insecurity and performance. Using a 3-wave design, anonymous survey data were collected online from a sample of 300 employees via Amazon Mechanical Turk. Time 1 job insecurity was curvilinearly related to Time 2 and Time 3 measures of job performance. In addition, these curvilinear relationships were largely attenuated among employees with higher levels of PsyCap. These results are discussed in light of rising job insecurity and the need for psychosocial interventions to attenuate its adverse effects. © 2017 Elsevier Ltd